Language & communication in primary schools - Allott, Kate; Waugh, David (David G.) (London : SAGE, 2016)
A guide for trainee and beginning teachers on how to use talk in the classroom. It explores the theory behind the teaching of language and communication skills and includes lots of practical advice on how to translate this into the classroom.
Early language development -- Creating the climate for successful communication -- Talk for learning -- Talking with children -- Language and communication in the English curriculum -- Planning fro and assessing speaking and listening -- Challenges : children's communication difficulties -- Language variation -- Speaking and listening : addressing the needs of EAL pupils / Kirsty Anderson -- Digital communication / John Bennett.
Keywords: English language -- Study and teaching (Primary); Oral communication -- Study and teaching (Primary)